Agricultural GDP, Agricultural Labor And Farmer Exchange Rate On Poverty In Sumatra Island: A Dynamic Panel Approach-GMM - Istikomah, Istikomah; Taufiqqurrachman, Fahrizal (Gorontalo State University, 2025)
This study aims to determine the effect of agricultural GRDP, agricultural labor, and farmer exchange rate on poverty on the island of Sumatra using a dynamic panel approach with the Generalized Method of Moments (GMM) method. The data type used is panel data covering 10 provinces on the island of Sumatra from 2017-2023. The method used is dynamic panel data regression analysis with the Generalised Method of Moments (GMM) method. The results showed that agricultural GRDP had a negative and insignificant effect on poverty, agricultural labor had a positive and significant impact on poverty and the farmer exchange rate (NTP) had a positive and insignificant impact on poverty. The government can encourage the growth of the agricultural sector by prioritizing export-oriented commodities and improving workers' ability through better skills training. In addition, assistance to farmers, especially in regulating selling prices at the farm level, diversifying agricultural products, improving the quality of agricultural products, and downstream agrarian products to encourage the agricultural sector, increasing technological intensity, and choosing the right method or cropping pattern.